Investment Project Selection by Applying COPRAS Method and Imprecise Data - Popovic, Gabrijela; Stanujkic, Dragisa; Stojanovic, Sanja (Serbian Journal of Management, 2012)
Investment projects can have a significant impact on the functioning and development of a company. Therefore, the selection of one or more investment projects from the set of possible is an important and difficult task for decision makers. This paper considers the investment projects selection based on financial analysis criteria and use of imprecise data. In the proposed model, the alternative projects performances are expressed using crisp and interval values, and then the best project from the available is selected by using COPRAS and COPRAS-G methods. A numerical example is given to demonstrate the applicability and effectiveness of the proposed approach.